Physiological and Pathological Mitochondrial Clearance Is Related to Pectoralis Major Muscle Pathogenesis in Broilers With Wooden Breast Syndrome - Hosotani, Marina; Kawasaki, Takeshi; Hasegawa, Yasuhiro; Wakasa, Yui; Hoshino, Maki; Takahashi, Naoki; Ueda, Hiromi; Takaya, Tomohide; Iwasaki, Tomohito; Watanabe, Takafumi (Frontiers in Physiology, 2020)
Wooden breast syndrome (WB) constitutes an emerging myopathy in the pectoralis major muscle (PM) of broiler chickens, characterized by myofiber hypertrophy and degeneration along with severe fibrosis. WB pathogenesis has been considered to involve hypoxia induced by rapid growth of the PM. In this study, we focused on mitochondrial morphology and dynamics in the myofibers as these organelles are sensitive to damage by hypoxia, and examined the effects on WB pathogenesis. Specifically, the PMs of a flock of 35 broilers at 55 days of age were evaluated. First, the severity of disease in each bird was determined by measuring histopathological indices including the fibrotic area (FA) in the muscle and circularity of myofibers (CM). These values were 29.4 ± 9.6% and 0.70 ± 0.042, respectively, showing variety among the flock. Myofiber vacuolization was observed in all birds including numerous small or large rimmed vacuoles, with the former consisting of ultrastructurally autophagosome-like vacuoles engulfing degenerated mitochondria. The large rimmed vacuoles frequently occurred in the PMs with more severe FA and CM, indicating a relationship between altered autophagy/mitophagy and WB severity. Next, the expression levels of hypoxia-adaptive and mitochondrial dynamics-related genes were analyzed and their correlations with the histopathological indices were examined. The histopathological indices were negatively correlated with the expression of vascular endothelial growth factor A (VEGFA), indicating that less angiogenesis owing to weakened hypoxia-inducible factor signaling induces more severe WB pathology. In addition, the observed negative correlation with mitochondrial dynamics-related genes implied that WB pathology deteriorates concomitant with reduced mitochondrial dynamics. Furthermore, the expression of mitochondrial dynamics-related genes showed strong positive correlation with that of VEGFA and autophagy/mitophagy-related genes. These results revealed that the PMs of broilers possess the mechanism of physiological clearance of mitochondria damaged by the hypoxia resulting from the continuous mitochondrial dynamics and autophagy/mitophagy accompanying rapid PM growth. In turn, the altered mitochondrial clearance induced by chronic hypoxia and the accumulation of damaged mitochondria likely underlies the severe pathological features of WB.